PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBANTUAN CANVA BERBASIS SEJARAH LOKAL “TENGKU AMIR HAMZAH” UNTUK SISWA KELAS IV SDN 056635 AIR HITAM - Lasmaida Br Siahaan, Theresia; aprillia, Rapita; Kumala Sari, Cut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The limited integration of local history into Social and Natural Sciences (IPAS) learning at the elementary school level highlights the need for more contextual learning media. This Research and Development (R&D) study aims to develop Canva-assisted instructional video media based on the local history of Tengku Amir Hamzah, while also evaluating its validity and practicality. Utilizing the 4D development model (Define, Design, Develop, Disseminate), this research involved fourth-grade students at SDN 056635 Air Hitam as subjects. Data were collected through observation, interviews, documentation, and questionnaires. The validation results indicated that the developed media was categorized as "highly valid," based on assessments from material experts (98%), language experts (98%), and media experts (90%). Furthermore, the practicality test achieved a 100% response rate from teachers and 90% from students, both falling into the "highly practical" category. It can be concluded that this Canva-based instructional video media is highly valid, practical, and feasible for implementation in fourth-grade elementary school IPAS learning.